1. Not finding help here? Sign up for a free 30min tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Derivatives of an odd function

  1. Jul 9, 2005 #1
    I've come to a few assumtions that my text hasn't covered yet, and I was hoping someone could confirm these for me or let me know where I might be missing something.

    Assuming f is an odd function and a > 0 and b > 0 and a < b:

    If f'(x) > 0 on (a,b), then f'(x) < 0 on (-b,-a).

    If f''(x) > 0 on (a,b), then f''(x) < 0 on (-b,-a).

    If lim (x->a) f(x) = inf, then lim (x->-a) f(x) = -inf

    If x = a is a vertical asymptote of f, then x = -a is also a vertical asymptote of f.

    If lim (x->inf) f(x) = L, then lim (x->-inf) f(x) = -L

    If y = L is a horizontal asymptote of f, then y = -L is also a horizontal asymptote of f.

    If f is odd and f is continuous on (-a,a), then f(0) = 0



    Thanks,
    hk
     
  2. jcsd
  3. Jul 9, 2005 #2
    The derivative of an odd function is an even function. Anything else you want to know can be taken from that.

    Also, to be "odd" requires that f(0) = 0. Figure out why.
     
  4. Jul 10, 2005 #3

    HallsofIvy

    User Avatar
    Staff Emeritus
    Science Advisor

    No! If f(x) is odd, then f'(x) is even. f' will have the same sign (indeed exactly the same values) for both (a,b) and (-b,-a).
    An easy example: if f(x)= x, then f'(x)= 1 for all x.
    Yes, this is true. If f(x) is odd, then f'(x) is even and f"(x) is odd again.
    Yes. Also if lim(x->)f(x)= L, then lim(x->-a)f(x)= -L.
    Yes. This is essentially just a restatement of the previous statement of "If lm(x->a) f(x)= inf, then lim(x->-a)f(x)= -inf".
    Yes. In fact, as above, this is true for (x-> any number) as well.
    Yes. This is just a restatement of "If lim(x->inf)= L, then lim(x->-inf)(f)= -L
    You don't need "and f is continuous on (-a,a)". If f is odd then f(-x)= -f(x) for all x. Taking x= 0, f(-0)= f(0)= -f(0) so 2f(0)= 0 and f(0)= 0.



     
  5. Jul 10, 2005 #4
    Thank you for your reply HallsofIvy, I have a better understanding now.

    hk
     
Know someone interested in this topic? Share this thread via Reddit, Google+, Twitter, or Facebook

Have something to add?



Similar Discussions: Derivatives of an odd function
Loading...